Modern methods to monitor end winding vibrations in turbo-generators. Issue 4 (1st July 2019) - Kreischer, Christian
Abstract : Purpose: Problems caused by end winding vibrations in power plant generators have become increasingly evident in recent years and reveal a need for monitoring and diagnostic systems. An increasing number of operational outages are caused by failures of the winding insulation or the conductor itself due to end winding vibrations. Meanwhile, it is clear that the condition of the end winding must be continuously monitored during operation to detect ineffective end winding support in time and to plan the repair. Design/methodology/approach: In this paper, the complex and nonlinear excitation mechanisms in large machines are presented and modern methods for vibration monitoring are described. Through a consistent use of vibration monitoring in the end winding area as well as the vibration diagnosis done by experts, damage mechanisms can be detected at an early stage, repair measures can be planned and serious damage owing to a weakened main insulation can be avoided. Findings: By combining modal analysis and trend monitoring in relation to the learned vibration behaviour, the end winding condition can be assessed in a differentiated manner and changes in the end winding structure can be detected early. Originality/value: Finally, an assessment for a two-pole, air-cooled turbo generator is proposed.